The Yiddish supernatural on screen: dybbuks, demons and haunted Jewish pasts - Margolis, Rebecca (Jewish science fiction and fantasy, 2024)
"This book examines how supernatural film and television integrate Yiddish dialogue to reimagine and reconstruct haunted and mystical elements of the Jewish experience, illustrating how closely bound up the Yiddish language is with shadowy immigrant pasts and the haunted sites of Holocaust memory"--